Karakterisasi Morfologis Pohon Aren (Arenga pinnata Merr.) di Kecamatan Talamau, Pasaman Barat - Exel Valentino Zebua; Aswaldi Anwar; Armansyah (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2025)
Sugar-palm is an industrial crop whose almost all parts can be utilized, potentially improving the wealth of the society and the national economy. Despite its great potential, the development of sugar palm in Indonesia is still low, so it is necessary to do breeding through exploration and morphological characterization of germ plasm. In Talamau, West Pasaman, sugar palm still comes from wild forest, there is potential for superior individuals that have not been optimally utilized. The purpose of this study was to obtain information on the character and germ plasm of sugar palm in Talamau, West Pasaman. The research was conducted in May-July 2024 in Talamau, West Pasaman. The method used was survey with descriptive data presentation. The sampling technique used was purposive sampling. The plants used as samples are plants that meet the specified criteria, namely having entered the generative phase and tapped by farmers. The results showed that there were 14 accessions of sugar palm trees in Talamau. From the accessions, the characters that have wide diversity are plant height, stem circumference, number of leaflets, leaflet length, male bunch distance, fruit diameter, fruit weight, and sap yield. While narrow diversity in the character of midrib length, rachis length, stalk length, number of female flower bunches, seed diameter, number of seeds, and soluble sugar content. Then based on cluster analysis, the accessions of sugar palm in Talamau are divided into two clusters separated by the surface character of palm fiber with a level of 0-35% dissimilarity.